Music Royalty Obligations and Copyright Enforcement in Commercial Public Spaces: The Case of Cafés and Restaurants in Indonesia - Dewi Ananda Putri; Muryanto Lanontji; Andi Muhammad Jafar (Al-Adalah: Jurnal Hukum dan Politik Islam, 2026)
Copyright constitutes a central pillar of intellectual property law in regulating the commercial exploitation of music as an economically valuable creative work. This article examines the legal obligation imposed on cafés and restaurants in Indonesia to pay music royalties under Government Regulation No. 56 of 2021, as an implementing instrument of Law No. 28 of 2014 on Copyright. Despite the existence of a formal regulatory framework, widespread non-compliance among café and restaurant business operators persists, raising significant juridical concerns regarding enforcement legitimacy and proportionality. Employing a normative-juridical research method with statutory and conceptual approaches, this study analyzes primary, secondary, and tertiary legal materials to assess the normative basis and legal implications of mandatory royalty payment obligations. The analysis demonstrates that the use of music in cafés and restaurants constitutes a form of public performance or communication to the public, thereby generating enforceable royalty obligations grounded in creators’ exclusive economic rights. Non-compliance gives rise to layered juridical consequences, encompassing administrative enforcement, civil liability, and the potential application of criminal sanctions under Indonesian copyright law. By situating the Indonesian regulatory framework within broader debates on copyright governance, this article contributes to the international discourse by clarifying how collective royalty regimes recalibrate the legal position of small and medium-sized commercial users in public performance rights enforcement systems.